Invasive management of non-ST elevation myocardial infarction (NSTEMI) in a patient with severe thrombocytopenia secondary to adult-onset immune thrombocytopenic purpura. Issue 12 (22nd December 2022) - Shah, Muhammad Usman; Muhammad, Asif; Davison, Benjamin; Naqvi, Syed Yaseen
Abstract : Managing patients with immune thrombocytopenic purpura (ITP) and thrombocytopenia is challenging when they present with acute coronary syndrome (ACS). They are at high risk of thrombotic events; however, antiplatelet medications may further lower the platelet count and predispose them to significant bleeding events, especially if undergoing percutaneous coronary intervention (PCI). We present a case of a man in his 70s, previously diagnosed with adult-onset ITP, admitted with ACS and severe thrombocytopenia. He was treated with a single antiplatelet and commenced on high-dose steroids. Once platelet levels had improved, he was started on second antiplatelet and underwent successful PCI with drug-eluting stent. He was safely discharged with dual antiplatelets for 1 month and then lifelong clopidogrel without any immediate complications. Our case shows that such patients, if stable, can be safely and successfully treated with steroids to improve platelet count before proceeding to invasive management and dual antiplatelet medications.